RANCANG BANGUN WEBSITE SEKOLAH DASAR ISLAM EL-SYABAB MENGGUNAKAN PHP DAN FRAMEWORK BOOTSTRAP - Taufik Hidayat; Sepriano Sepriano; Efitra Efitra (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
This research aims to develop a web design of El-Syabab Islamic Elementary School using the Rapid Application Development (RAD) system development method with PHP and Bootstrap. A qualitative approach is used with a focus on data collection through observation, interviews, and analysis of related documents. The results showed that website design succeeded in producing a el-syabab.sch.id website that makes it easier for schools to convey information online and as a medium for registration and promotion. PHP is used to develop logic and functionality, while Bootstrap is used for responsive design. Black-box test results show all features are working properly. The results of this study can be a practical guide for parties who want to develop websites quickly and effectively, and provide significant benefits for educational institutions in improving the efficiency of communication and administration through online media.